2011
DOI: 10.1371/journal.pone.0025894
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Blockade of TRPM8 Ion Channels Alters Cold and Cold Pain Responses in Mice

Abstract: TRPM8 (Transient Receptor Potential Melastatin-8) is a cold- and menthol-gated ion channel necessary for the detection of cold temperatures in the mammalian peripheral nervous system. Functioning TRPM8 channels are required for behavioral responses to innocuous cool, noxious cold, injury-evoked cold hypersensitivity, cooling-mediated analgesia, and thermoregulation. Because of these various roles, the ability to pharmacologically manipulate TRPM8 function to alter the excitability of cold-sensing neurons may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
172
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(191 citation statements)
references
References 48 publications
(131 reference statements)
9
172
3
1
Order By: Relevance
“…WT mice show robust cold allodynia 2 d after unilateral injections of the inflammatory agent complete Freund's adjuvant (CFA) (Fig. 1A) (P < 0.01, pre-vs. post-CFA or ipsilateral vs. contralateral), which we and others have previously reported (22)(23)(24). In contrast, Gfrα3 −/− mice show no differences in their hind paw lift latencies between the ipsilateral (inflamed) and the contralateral (control) sides, and there were no differences in their sensitivity compared with the basal, preinflamed state (Fig.…”
Section: Significancesupporting
confidence: 52%
See 3 more Smart Citations
“…WT mice show robust cold allodynia 2 d after unilateral injections of the inflammatory agent complete Freund's adjuvant (CFA) (Fig. 1A) (P < 0.01, pre-vs. post-CFA or ipsilateral vs. contralateral), which we and others have previously reported (22)(23)(24). In contrast, Gfrα3 −/− mice show no differences in their hind paw lift latencies between the ipsilateral (inflamed) and the contralateral (control) sides, and there were no differences in their sensitivity compared with the basal, preinflamed state (Fig.…”
Section: Significancesupporting
confidence: 52%
“…1B) (P < 0.01, preinjury vs. 7 d postinjury; P < 0.001, ipsilateral vs. contralateral), but cold sensitivity was remarkably unchanged in Gfrα3 −/− mice (ipsilateral vs. contralateral; preinjury vs. 7 d postinjury; P > 0.05). Lastly, one of the major side effects of platin-based chemotherapeutics is cold pain (26), a phenotype that can be modeled in mice given a single systemic injection of oxaliplatin (22,23). As with the previous pain models, the cold allodynia observed in WT mice (P < 0.001, basal vs. 7 d postinjection) was completely absent in mice null for GFRα3 ( Fig.…”
Section: Significancementioning
confidence: 67%
See 2 more Smart Citations
“…2 Notably, both TRPM8 agonists and antagonists exert analgesic effects: in particular, while TRPM8 agonists produce profound analgesia 2 at very low concentrations, even greater effects have been reported for TRPM8 antagonists. 3 This analgesia modulation represents a novel approach in a largely unmet therapeutic need. 4 Moreover, many studies have recently revealed novel potential pharmacological implications for TRPM8 modulators.…”
Section: Introductionmentioning
confidence: 99%